An exploratory sequential sentiment analysis of online learning during the movement control order in Malaysia - Abdul Rahman, Noorihan (Universiti Utara Malaysia Press, 2021)
Purpose – Online learning is an essential platform to support varying learning conditions, anytime and anywhere. It helps connect online communities regardless of one’s geographical location and time zone. During the COVID-19 outbreak in Malaysia, the use of online learning platforms has become a crucial option for accomplishing learning objectives. During this challenging time, universities have been looking for suitable solutions to address issues regarding the online learning process. This paper discusses the challenges in online learning, as well as the importance of collaborative learning activities during the Movement Control Order (MCO). Challenges in emotion and changes of routine among students have been detected during the MCO imposed by the government of Malaysia.